Undescended retropharyngeal parathyroid adenoma with adjacent thymic tissue in a 13-year-old boy with primary hyperparathyroidism. Issue 12 (31st December 2019) - Kordahi, Anthony M; Newfield, Ron S; Bickler, Stephen W; Mo, Jun Q; Khanna, Paritosh C; Bykowski, Julie; Bouvet, Michael
ABSTRACT: We describe a rare presentation of a symptomatic parathyroid adenoma located in an ectopic retropharyngeal position in a 13-year-old boy. Preoperative CT scan and MRI demonstrated the ectopic location of the parathyroid adenoma. The patient underwent successful parathyroidectomy with cure of his hyperparathyroidism. On pathologic exam, the specimen was made up of a parathyroid adenoma and adjacent thymic tissue, indicating that it was likely an undescended lower parathyroid gland arising from the third pharyngeal pouch. Ectopic retropharyngeal parathyroid adenomas are very rare and to our knowledge, none have been previously described in adolescents.